Clinical Observation on Low Back Pain Treated by DAVID Spinal System Core Muscles Training - Huazhong YANG; Lingjuan RAO; Zhili XU; Gaoming YUAN; Renming XIE (康复学报)
Objective:To observe the clinical effect of DAVID spinal system core muscles training on patients with chronic lower back pain.Methods:Sixty patients with chronic low back pain were randomly divided into experimental group and control group, with 30 cases in each group. The control group was given interference current therapy, conventional waist core strength training (bridge movement, lying leg raises, and elbow plank) and sling exercise training (SET).The experimental group was trained in interference current therapy and DAVID spine system training (F110 lumbar/thoracic extension test trainer, F120 lumbar/thoracic spin test trainer, F130 lumbar/thoracic anterior flexion tester).A semi-quantitative Oswestry disability index (ODI) and quantitative DAVID system assessment were applied to analyze the result before and after treatment.Results:With six weeks' treatment, pain relief, the ability of personal care, lifting, walking, sitting, standing and traveling, quality of sleep and social life, as well as evaluation of waist range of motion (ROM) of both groups improved obviously compared with that before, and the parameters of the experimental group was much better than that of the control group (P<0.05).Conclusion:DAVID spinal system core muscles training possess a significant improve effect on patients with chronic lower back pain.